Frequency of pain and eating disorders among professional and amateur dancers - Diogo, Maria Angélica Kurpel (2016)
CONTEXT AND OBJECTIVE: The pursuit of perfection can cause anxiety and lead dancers to exceed their physical limits. The aim here was to evaluate the prevalence of pain symptoms and eating disorders among professional and amateur dancers. DESIGN AND SETTING: Observational cross-sectional study; Curitiba, PR, Brazil. METHODS: Data on 150 professional and non-professional practitioners of ballet, jazz and street dance were collected through specific questionnaires: Brief Pain Inventory-Short Form (BPI-SF), Eating Attitudes Test-26 (EAT-26), Bulimic Investigatory Test Edinburgh (BITE) and State-Trait Anxiety Inventory-T-6 (STAI-T-6). RESULTS: Pain was observed in 58.6% of the sample, equally between professionals and amateurs (P = 0.19). Ballet dancers had more lower-limb pain than the other groups (P = 0.05). EAT-26 showed a tendency towards more eating disorders among the amateurs (P = 0.06). Higher risk of eating disorders was found among ballet dancers (P = 0.004) and jazz practitioners (P = 0.02) than among street dancers. Amateurs had more symptoms on the BITE scale (P < 0.0001), more pain (P = 0.002) and higher anxiety (P < 0.0001). Eating disorders were more common among females (P = 0.01) and singles (P = 0.02). Professionals were more satisfied with their own body image than amateurs (P < 0.001). CONCLUSIONS: Pain symptoms were found in almost half of the sample, equally among professionals and amateurs as well as between the three dance styles. Female and singles had more eating disorders. Those with eating disorders had higher levels of pain and anxiety.